Pengaruh Saham Syariah dan Reksadana Syariah terhadap Pertumbuhan Ekonomi di Indonesia - Rheva Berliana; Silvia Lovita; Sintia Eka Wulandari; Esty Apridasari (Indo Publishing, 2025)
This study examines the effect of sharia stocks and sharia mutual funds on economic growth in Indonesia. Using a quantitative approach, this study analyzes data from 2016 to 2022 obtained from the Central Statistics Agency and the Financial Services Authority. The independent variables in this study are sharia stocks (represented by the Jakarta Islamic Index/JII and the Indonesia Sharia Stock Index/ISSI) and sharia mutual funds, while the dependent variable is economic growth. Data analysis was performed using classical assumption tests and multiple linear regression with the help of Eviews 10 software, including F test and t test. The results show that partially, sharia stocks have a significant effect on economic growth in Indonesia. The increasing investment interest in the sharia capital market, especially sharia stocks, contributes to increasing economic growth, poverty reduction, and job creation. On the other hand, sharia mutual funds partially do not have a significant effect on economic growth. This is allegedly due to the allocation of sharia mutual fund portfolios by investment managers tending to be in large-cap company stocks that tend to be stagnant. However, simultaneously, sharia stocks and sharia mutual funds have a significant effect on economic growth in Indonesia.